Five isomers of monomeric cytosine and their interconversions induced - Lapinski, Leszek (2011)
Photoisomerization processes involving five isomers of cytosine were induced by narrowband tunable UV irradiation of matrix-isolated monomers of the compound. Irradiation of an argon matrix containing cytosine monomers with UV l = 313 nm laser light resulted in syn2anti photoisomerizations between the two imino–oxo forms, whereas the substantially more populated amino–hydroxy and amino–oxo forms stayed intact. Subsequent irradiation with shorter-wavelength UV l = 311 nm laser light led to two concomitant phototautomeric processes consuming the amino–oxo isomer: (i) an oxo - hydroxy hydrogen-atom transfer photoprocess converting the amino–oxo form into the amino–hydroxy tautomer; (ii) amino - imino hydrogen-atom transfer converting the amino–oxo form into the imino–oxo isomers. The UV-induced phototransformations, together with mutual conversions of the two amino–hydroxy conformers induced by irradiation with narrowband NIR light, allowed positive detection and identification of the five isomeric forms of monomeric cytosine. This is the first experimental observation of all five low-energy isomers of cytosine.